CHARACTERISTICS OF JOURNALISTIC ACTIVITY IN EMERGENCIES AND SITUATIONS (American Journal of Pedagogical and Educational Research, 2024)
An emergency situation is a situation that can lead to the death of people, damage to people's health or the environment, great material damage to people's life and its disruption in a certain area. it is a situation caused by an accident, disaster, natural disaster, epidemics, epizootics.